Reactivity of Thiol-Rich Zn Sites in Diacylglycerol-Sensing PKC C1 Domain Probed by NMR Spectroscopy - Cole, Taylor R.; Igumenova, Tatyana I. (Frontiers in Molecular Biosciences, 2021)
Conserved homology 1 (C1) domains are peripheral zinc finger domains that are responsible for recruiting their host signaling proteins, including Protein Kinase C (PKC) isoenzymes, to diacylglycerol-containing lipid membranes. In this work, we investigated the reactivity of the C1 structural zinc sites, using the cysteine-rich C1B regulatory region of the PKCα isoform as a paradigm. The choice of Cd2+ as a probe was prompted by previous findings that xenobiotic metal ions modulate PKC activity. Using solution NMR and UV-vis spectroscopy, we found that Cd2+ spontaneously replaced Zn2+ in both structural sites of the C1B domain, with the formation of all-Cd and mixed Zn/Cd protein species. The Cd2+ substitution for Zn2+ preserved the C1B fold and function, as probed by its ability to interact with a potent tumor-promoting agent. Both Cys3His metal-ion sites of C1B have higher affinity to Cd2+ than Zn2+, but are thermodynamically and kinetically inequivalent with respect to the metal ion replacement, despite the identical coordination spheres. We find that even in the presence of the oxygen-rich sites presented by the neighboring peripheral membrane-binding C2 domain, the thiol-rich sites can successfully compete for the available Cd2+. Our results indicate that Cd2+ can target the entire membrane-binding regulatory region of PKCs, and that the competition between the thiol- and oxygen-rich sites will likely determine the activation pattern of PKCs.